Peran Enzim Protease Endogenus dalam Proses Pelunakan Daging Selama Post Mortem - Sri Raharjo (agriTECH, 1996)
Proteolysis of myofibrill ar proteins is responsible for structural degradation in skeletal muscle leading to meat tenderization. Among endogenous proteases involved in post mortem proteolysis, only calpains (calcium-dependent proteolytic systems) have been proven of having a predominant role in post mortem tenderization. Ca 1p ai n.s consist of Âµ.-calpain (proteinase requiring 5-701.1M Ca2+ for activity), m-calpain (proteinase requiring 100 - 2000 /.i.M ca'* for activity), calpastatin (a specific inhibitor to calpains and it also requires Cat` to bind to the proteinases). Although calpastatin is a well known inhibitor for calpains activity, present knowledge on the regulation of calpain activity is by no means complete. However, there is no doubt that there are factors other than proteolysis such as elevated ionic strength and presence of connective tissues that will certainly affect meat tenderness.